The Problem of the Economic Rights of Indigenous Peoples in Convention 169 of the International Labor Organization - Naranjo-Luzuriaga, Edison Joselito (2022)
The article analyzes The International Labor Organization (ILO) Convention 169 in attention to the issue of the economic rights of indigenous peoples. The poverty in which the indigenous peoples remain is taken as a premise. Based on this, the following aspects related to economic rights are examined: ambiguity in the formulation of said rights; the conception of indigenous peoples as passive agents; the diffuse meaning of economic rights; its conception from the subsistence criterion; the limits of prior consultation; and the right to employment. By way of conclusion, the problem of the equivocal and remedial formulation of economic rights is revealed.